Glucose starvation induces resistance to metformin through the elevation of mitochondrial multidrug resistance protein 1 - Hwang, Sung‐Hyun; Kim, Myung‐Chul; Ji, Sumin; Yang, Yeseul; Jeong, Yeji; Kim, Yongbaek (Cancer science, 2019)
Metformin, a drug for type 2 diabetes mellitus, has shown therapeutic effects for various cancers. However, it had no beneficial effects on the survival rate of human malignant mesothelioma (HMM) patients. The present study was performed to elucidate the underlying mechanism of metformin resistance in HMM cells. Glucose‐starved HMM cells had enhanced resistance to metformin, demonstrated by decreased apoptosis and autophagy and increased cell survival. These cells showed abnormalities in mitochondria, such as decreased ATP synthesis, morphological elongation, altered mitochondrial permeability transition pore and hyperpolarization of mitochondrial membrane potential (MMP). Intriguingly, Mdr1 was significantly upregulated in mitochondria but not in cell membrane. The upregulated mitochondrial Mdr1 was reversed by treatment with carbonyl cyanide m‐chlorophenyl hydrazone, an MMP depolarization inducer. Furthermore, apoptosis and autophagy were increased in multidrug resistance protein 1 knockout HMM cells cultured under glucose starvation with metformin treatment. The data suggest that mitochondrial Mdr1 plays a critical role in the chemoresistance to metformin in HMM cells, which could be a potential target for improving its therapeutic efficacy. This study illustrated that glucose‐deficient conditions facilitated resistance to metformin in human malignant mesothelioma (HMM) cells through Mdr1 increasing in defected mitochondria. It also increased through mitochondrial membrane potential hyperpolarization and mitochondrial dysfunction rescued glucose‐starved HMM cells as a result of metformin treatment.